SEX DAN GENDER: APA DAN MENGAPA - Marcellinus Molo (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1993)
This article introduces the elementary concepts, such as feminist perspective, sex, gender, and gender relations. Sex is a biological fact. The individual's quality and capacity and the roles derived from them, are difined along sex lines. During a long history, this perspective has been accepted in society. The dichotomy of ideal roles for both males and females, was the manifestation of such a statusquo.Criticisms to the division of quality and roles was based on the reason that the ideal roles was not a result of natural process, but of social processes and cultural transformations, under the dominant male culture. Gender has also been used for deconstructing the statusquo. Discourse and counter-discourse processes has been directed towards deconstruction both at the ideological and behavioral levels.